Animal models in alcoholic pancreatitis: what can we learn? - Schneider, Alexander; Whitcomb, David C.; Singer, Manfred V. (Pancreatology, 2002)
Although the majority of patients with chronic pancreatitis present a history of excessive alcohol consumption, the pathophysiology underlying chronic alcoholic pancreatitis remains poorly defined. Since experimental animal models represent helpful tools in understanding human disease, numerous laboratory studies have been designed to study the effects of alcohol on the pancreas. In the present article we summarize the existing animal models that have been used to investigate the effects of acute and chronic alcohol application on the development of morphological alterations and pancreatic injury. Despite considerable experimental effort, acute or chronic ethanol feeding alone failed to cause acute or chronic pancreatitis in animals. However, ethanol-feeding and the combination with other procedures has demonstrated several mechanisms that play a role in ethanol-induced pancreatic injury. Among these ethanolinduced alterations and mechanisms are the reduction of pancreatic blood-flow and microcirculation, damaging effects of ethanol metabolites, increased pancreatic acinar cell expression of digestive and lysosomal enzymes, increased glandular enzyme content, additional nutritional factors, pancreatic duct obstruction, and limitations of pancreatic regeneration. Although no satisfactory animal model for alcoholic pancreatitis has been developed, these animal models have provided insights in several factors that predispose the pancreas to development of pancreatic injury and contribute to alcoholic pancreatitis.